Adherence to Cardiovascular Therapy Medications and Factors Associated with Non-Adherence among Cardiac Patients’ Who Attending Outpatient Clinic at Al Nasiriyah Heart Center - Qasim Ali Khasal (Pakistan Journal of Medical & Health Sciences, 2022)
Background: non-adherence to medication among patients with cardiovascular disease is often the major factor that causing poor clinical outcomes ,high mortality rates and consequently higher healthcare costs. The literature evaluating the prevalence of and reasons for non-adherence in settings with poor resource is extremely limited compared with resource-rich settings. There is a lack of data about adherence to cardiovascular therapy medications in Iraq hence this study was conducted to identify prevalence, predictors as well as barriers of non-adherence to medication among cardiovascular disease patients’ in An Nasiriyah city. Methods :a descriptive, cross-sectional study design was carried out at An Nasiriyah Heart Center in Al- Nasiriyah city for period from January 8, 2021 to July 5, 2021. A purposive (non- probability) sample of 195 patients with cardiovascular disease were included. Constructed questionnaire and the process of the self-administrative report were used to collect data. The questionnaire involves of 3 parts: part 1includes Patients socio-demographic and Clinical information . Part 2: involve of patient responses to the adherence with medication regimen . Part 3: involve of factors associated with non-adherence to Medication. Panel of experts determined content validity of the instrument, as well as the internal consistency of the instrument was determined through the pilot study and the calculation of Alpha Correlation Coefficient (0.83). Adherence to Cardiovascular therapy medications is assess through use the Medication Compliance Questionnaire . Factors influencing non-adherence to cardiovascular therapy medications , were determined through application of adjusted basis and multiple logistic regression models. Results: study result showed that the prevalent for non-adherence to cardiovascular drug was (54.4%) . The top four barriers for poor cardiovascular therapy medications adherence among the study participants were the forgetfulness of take dose for medications 59(44.4%), financial strain34 (25.6%) , multiple medication15 (11.3%) and 15 (11.3%) Too busy. In multivariable analysis, participants who were age group > 60 years and number of medication uses were more likely to be non-adherent to their cardiovascular medications . Conclusions: the current study concluded that the adherence to cardiovascular medications is poor where more than half of study participants being nonadherent.